Neglected double-J stent presenting as giant bladder and ureteral stone: A case report - Muhammad Fachri Fauzi, MD; Tarmono Djojodimedjo, MD; Johan Renaldo, MD (Radiology Case Reports, 2024)
Implementing double-J (DJ) stents in urological practice helps to alleviate kidney and ureteral obstruction. The primary causes of neglecting a DJ stent typically involve inadequate counseling and poor patient compliance. Encrustations of neglected DJ stents present a significant challenge. This study aims to report on a neglected DJ stent that persisted for 3 years, presenting as giant bladder and ureteral stones. We report on a 35-year-old male with chief complaints of discomfort in the suprapubic and left flank, along with concurrent micturition leakage. He had a DJ stent implanted to treat his ureteral stone 3 years ago. Advanced imaging showed a left distal ureteral stone (0.7×0.8×1.9 cm), extensive hydronephrosis and hydroureter, and a bladder stone (4.7×3.9×3.2 cm). A left ureterorenoscopy (URS) was done to remove a stone from the end of the ureter, half of a DJ stent and a bladder calculus using cystolitholapaxy. However, the patient underwent a second surgery owing to a residual bladder stone. The patient was discharged from the hospital without any symptoms. A foreign object in the urinary tract, like a DJ stent, may create secondary calculi. Endoscopic treatment could improve the efficacy of treating large bladder stones simultaneously with ureteral stones. As a measure to prevent DJ stent-related complications, it is also essential for healthcare professionals to provide information and follow-up care to patients regarding the use of DJ stents.